2017
DOI: 10.1016/j.ijrmhm.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

A study on the sintering of ultrafine grained tungsten with Ti-based additives

Abstract: Tungsten (W) is a brittle material at room temperature making it very difficult to fabricate. Although the lack of ductility remains a difficult challenge, nano-sized and ultrafine grain (UFG) microstructures offer potential for overcoming tungsten's room temperature brittleness. One way to manufacture UFG W is to compact and sinter nanosized W powder, however, it is a non-trivial task to control grain growth during sintering. In an effort to inhibit grain growth, the effect of Ti-based additives on the densif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…[ 77,116,137 ] b) Grain coarsening index (from initial particle size to bulk grain size) versus relative density, for comparison of the differently sized pure W powders. [ 50,77,88,91,98,117,125,130,135,136,138–141 ] c) Comparison of grain size of pure W versus various ODS W, plotted with relative density. [ 47,50,71,75,117,133,142–149 ]…”
Section: Recent Progress In Sintered Refractory Metals Alloys and Com...mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 77,116,137 ] b) Grain coarsening index (from initial particle size to bulk grain size) versus relative density, for comparison of the differently sized pure W powders. [ 50,77,88,91,98,117,125,130,135,136,138–141 ] c) Comparison of grain size of pure W versus various ODS W, plotted with relative density. [ 47,50,71,75,117,133,142–149 ]…”
Section: Recent Progress In Sintered Refractory Metals Alloys and Com...mentioning
confidence: 99%
“…[77,116,137] b) Grain coarsening index (from initial particle size to bulk grain size) versus relative density, for comparison of the differently sized pure W powders. [50,77,88,91,98,117,125,130,135,136,[138][139][140][141] c) Comparison of grain size of pure W versus various ODS W, plotted with relative density. [47,50,71,75,117,133,[142][143][144][145][146][147][148][149] Field-assisted sintering utilizes the external pressure, electric, microwave, and coupled multi-physic fields to improve sintering.…”
Section: Tungstenmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al studied the effect of Ti addition on the densification and grain growth of W powders in the sintering process 59 . The results showed that with 1 wt.% Ti addition, the mean grain size of W was decreased by 63% compared with that without Ti but with the same sintering density.…”
Section: Interaction With W/cu Interfacementioning
confidence: 99%